Does the inclusion of electronic polarisability lead to a better modelling of peptide aggregation?. Issue 32 (21st July 2022) - Kav, Batuhan; Strodel, Birgit
Abstract : Simulating the process of amyloid aggregation is a hard task. We test whether the inclusion of electronic polarisability as done in CHARMM-Drude improves the modelling of Aβ16–22 aggregation and find it does not. Reasons for the failure are given. Abstract : Simulating the process of amyloid aggregation with atomic detail is a challenging task for various reasons. One of them is that it is difficult to parametrise a force field such that all protein states ranging from the folded through the unfolded to the aggregated state are represented with the same level of accuracy. Here, we test whether the consideration of electronic polarisability improves the description of the different states of Aβ16–22 . Surprisingly, the CHARMM Drude polarisable force field is found to perform worse than its unpolarisable counterpart CHARMM36m. Sources for this failure of the Drude model are discussed.